2004
DOI: 10.1093/ageing/afh062
|View full text |Cite
|
Sign up to set email alerts
|

Inhaler technique in older people in the community

Abstract: Metered dose inhaler was the most frequently prescribed inhaler and was used correctly by most subjects especially in combination with large volume spacers. Major errors were more common with breath-actuated devices. Inhaler technique should be checked as patients' perception of their inhaler skills correlates poorly with actual performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 11 publications
2
50
2
2
Order By: Relevance
“…Correct inhaler technique is essential for the most effective delivery of inhaled drugs; however, a number of studies have identified that errors in inhaler technique are common [2, [12][13][14][15]. Errors in inhaler technique are associated with suboptimal delivery of the drug into the lungs and may also potentially increase the risk of adverse effects, particularly with inhaled corticosteroids, but despite this, one study demonstrated that approximately a fifth of older patients receiving inhaled therapy could not recall receiving inhaler technique training [16].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Correct inhaler technique is essential for the most effective delivery of inhaled drugs; however, a number of studies have identified that errors in inhaler technique are common [2, [12][13][14][15]. Errors in inhaler technique are associated with suboptimal delivery of the drug into the lungs and may also potentially increase the risk of adverse effects, particularly with inhaled corticosteroids, but despite this, one study demonstrated that approximately a fifth of older patients receiving inhaled therapy could not recall receiving inhaler technique training [16].…”
Section: Reviewmentioning
confidence: 99%
“…In a UK based study of people over the age of 70 years living at home, 15.8% of subjects were using an inhaler, of whom 42.8% were using a metered-dose inhaler (MDI) [16]. Despite their wide prescription many patients cannot use pMDIs correctly, even with education and training [13,18,19].…”
Section: Pressurized Metered-dose Inhalersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, another study [78] aimed at comparing MDIs with large volume spacers with breathactivated inhalers and DPIs in the elderly demonstrated that the latter were more likely to be used correctly than inhalers with large volume spacers. Despite some of the above-reported evidence and the generally accepted view that older people use conventional MDIs poorly, MDIs seem to be the most frequently employed type of inhaler device amongst older people in the community, and are used adequately when in combination with large volume spacers [79]. However, this study excluded patients with cognitive impairment, likely underestimating the rate of failure to use inhalers properly in the community.…”
Section: Practical Considerations For Elderly Patients On Long-term Dmentioning
confidence: 91%